1998
DOI: 10.1159/000044967
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and Serotonin in Uremic Pruritus: Effect of Ondansetron in CAPD-Pruritic Patients

Abstract: Pruritus is a common, unpleasant symptom of uremic patients. Serotonin and histamine have been reported as possible mediators of uremic pruritus, and ondansetron is a potent and selective inhibitor of 5-HT3 receptors. The aims of our study were (1) to evaluate the effect of ondansetron on uremic pruritus in continuous ambulatory peritoneal dialysis (CAPD) patients and its safety and (2) to investigate the role of histamine and serotonin in uremic pruritus. To study the prevalence and pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 18 publications
0
81
0
6
Order By: Relevance
“…One goal of the present study was therefore to investigate which 5-HT receptor subtypes are involved in acute scratching elicited by intradermal 5-HT in the rat. Although 5-HT 3 receptors have been implicated in itch associated with cholestasis, uremia, and spinal opioids (Schworer et al, 1995;Balaskas et al, 1998;Kyriakides et al, 1999), 5-HT 3 receptor antagonists did not affect scratching elicited by intradermal 5-HT in mice, in contrast to the blockade of scratching by 5-HT 2 antagonists (Yamaguchi et al, 1999). These data argue against a role for 5-HT 3 receptors in acute evoked scratching in mice.…”
mentioning
confidence: 84%
“…One goal of the present study was therefore to investigate which 5-HT receptor subtypes are involved in acute scratching elicited by intradermal 5-HT in the rat. Although 5-HT 3 receptors have been implicated in itch associated with cholestasis, uremia, and spinal opioids (Schworer et al, 1995;Balaskas et al, 1998;Kyriakides et al, 1999), 5-HT 3 receptor antagonists did not affect scratching elicited by intradermal 5-HT in mice, in contrast to the blockade of scratching by 5-HT 2 antagonists (Yamaguchi et al, 1999). These data argue against a role for 5-HT 3 receptors in acute evoked scratching in mice.…”
mentioning
confidence: 84%
“…Ondansetron has been shown to be effective for the treatment of certain cases of uremic pruritus (6,14), but this finding has been refuted by another study (15). Some studies showed that neuraxial opioid-induced pruritus respond to prophylaxis (3,16,17) and treatment (5,18) with ondansetron.…”
Section: Discussionmentioning
confidence: 99%
“…Le prurit n'a pas répondu à un traitement classique aux antipruritiques, mais a répondu à l'ondansétron, un antagoniste sélectif des récepteurs 5-hydroxytryptamine de type 3. O ndansetron is effective against chemotherapy-induced and postoperative nausea and vomiting (1,2). Over the past few years, several publications reported on the efficacy of ondansetron in treating neuraxial opioid-induced pruritus (3)(4)(5) and uremic pruritus in continuous ambulatory peritoneal dialysis (6). The current report presents a case of a child suffering from chronic pruritus refractory to conventional antipruritic drugs who was successfully treated with ondansetron.…”
mentioning
confidence: 91%
“…Serotonin levels were also increased in CKD associated pruritus. Serotonin may cause itching by stimulating a 5-HT 3 receptor ondansetron and granisetron which have shown conflicting results regarding their effectiveness in relieving itch in patients [19][20][21].…”
Section: Mast Cellsmentioning
confidence: 99%